What can we learn from HIV, COVID‐19 and mpox stigma to guide stigma‐informed pandemic preparedness? - Logie, Carmen H. (Journal of the International AIDS Society, 2022)
[...]the third stigma archetype targets persons with a “visible” health condition [ 3], aligning with the importance of considering concepts of peril, visibility and controllability [ 10]. Drivers: — prejudice, stereotypes and judgement experienced by affected communities (e.g. sex workers and men who have sex with men [MSM]) Facilitators:— criminalization (e.g. of sex work, LGBTQ persons, HIV non-disclosure) — ethno-racial, MSM and socio-economic disparities in HIV Drivers:— prejudice, stereotypes and judgement of Asian communities — social value of groups impacted by COVID-19 Facilitators: — criminalization of public health responses — policies for accessing vaccines, testing and sick leave — occupational safety standards Drivers: — prejudice, stereotypes and judgement experienced by MSM — community awareness of mpox Facilitators:—health policies regarding mpox testing, vaccination and treatment — health policies for sick leave and medical care access — ethno-racial and MSM healthcare disparities Assess peril, visibility and controllability Peril: How dangerous is the infection considered? Peril: — extent of HIV treatment literacy Visibility:—signs of health conditions linked with HIV (e.g. Kaposi sarcoma) Controllability: — blame of key populations for HIV acquisition and transmission Peril: — mortality and perceived severity of COVID-19 Visibility: — visible Asian ethno-racial minority persons targeted by anti-Asian racism Controllability: — blame for becoming infected with COVID-19 Peril: — severity of illness with mpox Visibility: — visibility of lesions and illness Controllability: — blame of persons with mpox, including MSM, for their infection Identify community strengths What social histories of solidarity, mutual support and collective care exist among affected communities? What community strengths can be leveraged in pandemic responses? — LGBTQ community-groups and AIDS service organizations that support affected communities — histories of HIV activism and mutual support — mutual support or poverty alleviation networks for people who miss or lose employment due to COVID-19 infection, quarantine and/or lockdowns — anti-racist solidarity movements — LGBTQ community-groups and AIDS service organizations to support affected communities — community care networks to help persons access and locate vaccines and social/financial support if quarantined — global vaccine equity movements and advocacy for vaccine access in Africa Activism, advocacy and collective care initiatives led by lesbian, gay, bisexual, transgender and queer communities in the HIV epidemic—and in mpox community-based responses [ 2]—can reduce social isolation and experiences